Improving Students' Competence Of Reading Comprehension Through Reciprocal Teaching Strategy (An Action Research in the Eleventh Grade Students atSMAN 2 Boyolali in the Academic Year of 2011/2012) - Purwaningsih, Retno, Prof. Dr. Joko Nurkamto, M.Pd, Drs. H. Maryadi, M.A (2014)
The students' problem was that most of them had low competence in reading comprehension. The problem appears due to some causes. Among others are (1) the lack of students' motivation, (2) the lack of opportunities for collaboration, and (3) the lack of opportunities to use reading strategies directly. The objectives of the study are: (1) to find out whether or not the application of reciprocal teaching strategy can improve students' reading comprehension, (2) to find out the effectiveness of reciprocal teaching strategy in the learning of reading comprehension. This research was carried out at SMAN 2 Boyolali. It was held for about 10 months, from July 2011 to May 2012. The subjects of the research are the students of grade XI Social 3 which consists of 14 male students and 17 female ones. The type of the study is a classroom action research. The procedures are based on Elliot's model. Research data are obtained through three techniques: observation, interview, and documentation. Qualitative data were analyzed by using technique of qualitative description analysis, while quantitative data were analyzed by using technique of comparative description analysis. The study shows that reciprocal teaching strategy gives some positive effects: (1) the test result in each cycle (cycle 1, 2, and 3) shows that students made a positive improvement. The average scores in pre-test, cycle 1, cycle 2, and cycle 3 are respectively 56.39, 60.13, 64.65, 68.26. The percentage of improvement in the average score is 21.05. It shows that the percentage of improvement from pre-test to post-test in cycle 3 is significant. (2) the learning process runs effectively. It means that reciprocal teaching strategy is effective in the learning of reading comprehension. Most students participated well and actively during the learning process. They were motivated to take part in the instructional activity. Moreover, they were eager to work cooperatively. Therefore, it is suggested that English teachers use reciprocal teaching strategy in the learning of reading comprehension. It is also suggested that other researchers carry out such a research by developing other language skills as well as other subjects. Finally, it is recommended that the institution do socialization about what reciprocal teaching is. This way, teachers have an alternative strategy to overcome their problems in the learning process.